Earth Resistance and Earth Construction To Interference Currents On Swamp Land - Putra, Dian Eka; Nawawi, Zainuddin; Jambak, Muhammad Irfan (International Conference on Sciences Development and Technology, 2022)
To protect electrical power installation equipment, especially that in open areas where it is particularly vulnerable to both technical and non-technical disturbances, such as those frequently brought on by lightning surge currents that result in large fault currents, it is crucial to build a grounding installation. A good and trustworthy grounding system is required to flow this significant fault current, both in terms of a low grounding resistance value and the grounding system's design. There are several high voltage transmission towers or electrical power installation tools in open spaces, and they are built on a variety of soil types, including 150 kV transmission towers built on swamp land. The measurements on the shampooing marsh terrain yielded the maximum and minimum values, with the maximum value occurring at a depth of 1 meter and a earth resistance value of 25.70 Ω and the minimum occurring at a depth of 2 meters and a earth resistance value of 12.10 Ω, respectively. Based on the findings of these measurements, a grounding grid construction employing four electrode rods of two distinct types copper-coated iron rods and galvanized iron rods each measuring 3.5 meters in length was designed using the CYMGRD application. Through the CYMGRD application, a different Ground Potential Rise (GPR) is obtained; with the same fault current of 10234.6 Ampere, the GPR value for the copper-coated rod construction is 54.7871 volts as opposed to the galvanized rod construction's 55.0625 volts.